2021
DOI: 10.1136/bmjopen-2020-048107
|View full text |Cite
|
Sign up to set email alerts
|

Challenges facing essential workers: a cross-sectional survey of the subjective mental health and well-being of New Zealand healthcare and ‘other’ essential workers during the COVID-19 lockdown

Abstract: ObjectivesTo compare psychological outcomes, experiences and sources of stress over the COVID-19 lockdown in New Zealand in essential workers (healthcare and ‘other’ essential workers) with that of workers in nonessential work roles.DesignOnline cross-sectional survey.SettingConducted in New Zealand over level 4 lockdown in April/May 2020.ParticipantsFindings from employed participants (2495) are included in this report; 381 healthcare workers, 649 ‘other’ essential workers and 1465 nonessential workers.Primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 41 publications
6
31
0
1
Order By: Relevance
“…Our findings reflect observations elsewhere [25,26]; a survey conducted in April-May 2020 in Melbourne (Australia) showed marked levels of depression, anxiety, and post-traumatic stress disorder among healthcare workers, despite the relatively low levels of COVID-19 exposure [26]. In NZ, a survey of healthcare workers' mental health during the COVID-19 pandemic found that 71% were at a greater risk of moderate levels of anxiety than non-essential workers [27].…”
Section: Discussionsupporting
confidence: 83%
“…Our findings reflect observations elsewhere [25,26]; a survey conducted in April-May 2020 in Melbourne (Australia) showed marked levels of depression, anxiety, and post-traumatic stress disorder among healthcare workers, despite the relatively low levels of COVID-19 exposure [26]. In NZ, a survey of healthcare workers' mental health during the COVID-19 pandemic found that 71% were at a greater risk of moderate levels of anxiety than non-essential workers [27].…”
Section: Discussionsupporting
confidence: 83%
“…, 2021), while coping with new and extreme workplace stressors (Carnevale and Hatak, 2020). Tasked with the unexpected responsibility of reducing possible health hazards for customers and coworkers, the stress and anxiety of frontline work has been substantial (Mayer et al , 2022; Bell et al. , 2021; Czeisler et al.…”
Section: Introductionmentioning
confidence: 99%
“…Supermarket personnel were required to take on additional roles to educate staff and customers as well as implement operational changes such as one-way traffic in stores and enhanced cleaning protocols (Shumsky et al, 2021), while coping with new and extreme workplace stressors (Carnevale and Hatak, 2020). Tasked with the unexpected responsibility of reducing possible health hazards for customers and coworkers, the stress and anxiety of frontline work has been substantial (Mayer et al, 2022;Bell et al, 2021;Czeisler et al, 2020). The impacts of these stressors are not yet well understood, emphasizing the need to track the well-being of this frequently overlooked socioeconomically vulnerable workforce, as the extant literature on COVID-19 exposure risks and health consequences among frontline workers neglects hazards specific to non-healthcare occupations.…”
Section: Introductionmentioning
confidence: 99%
“…While the stringent lockdowns led to prolonged success in eliminating COVID-19 during 2020, this came with a psychological toll [ 47 , 48 , 49 ], particularly amongst those with pre-existing mental health conditions [ 48 , 50 ], youth [ 51 ] and younger adults [ 50 ], and essential workers [ 52 ]. This psychological toll was seen in increased overdose and self-harm hospital presentations and significant increases in ambulance callouts nationally for mental health conditions over lockdown [ 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%